(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This article examines the role of colloquial restricted units—such as idioms, slang, and conversational expressions—in the poetics of a literary work. It analyzes how these elements contribute to authenticity, character development, and emotional impact within a text. The article discusses the effectiveness of using colloquial language to reflect the realities of everyday speech and create vivid, relatable characters. Through literary examples, the study demonstrates how restricted colloquial units enhance expressiveness, enrich imagery, and support the author’s artistic goals, ultimately deepening the reader’s engagement with the narrative.